Movement disorders in systemic autoimmune diseases: clinical spectrum, ancillary investigations, pathophysiological considerations - Menozzi, Elisa; Mulroy, Eoin; Akbarian-Tefaghi, Ladan; Bhatia, Kailash P.; Balint, Bettina (Parkinsonism & related disorders, 2021)
With the advances in neuroimmunology especially due to the discovery of new neuronal antibodies, the recognition of treatable antibody-related movement disorders has recently received much attention. In contrast, the identification and characterisation of movement disorders associated with systemic autoimmune diseases remains a substantially unexplored area. Beyond the classic few associations such as chorea and antiphospholipid syndrome, or ataxia and coeliac disease, movement disorders have been reported in association with several systemic autoimmune diseases, however a clear image of clinical phenotypes, investigations, and treatment outcomes in these conditions has never been drawn. In this review, we analyse data from approximately 300 cases and summarise the epidemiological, clinical and diagnostic features of movement disorders associated with systemic autoimmune diseases, and the available knowledge about treatment and outcomes. We highlight that movement disorders in systemic autoimmune conditions are frequently the only or among a few presenting manifestations and are mostly treatable disorders responding to immunotherapy or dietary modifications. We point out the pertinent combination of clinical features and investigations which can suggest the underlying autoimmune nature of these movement disorders, and thus address the most appropriate treatment.
Gesehen am 16.08.2021